Enhancing Students’ Critical Thinking Skills through IMOREAR: An AR-Based Renewable Energy Module - Lina Aviyanti; Nuzulira Janeusse Fratiwi; Abdul Salam; Silmi Fitriani; Khairunnisah Khairunnisah; Abu Nawas (Journal of Natural Science and Integration, 2026)
Critical thinking skills are essential competencies in renewable energy learning, requiring evidence-based analysis, evaluation, and informed decision-making. This study aimed to enhance students’ critical thinking skills through an Interactive E-Module on Renewable Energy Using Augmented Reality (IMOREAR). The study employed a pre-experimental one-group pretest–posttest design involving 30 high school students (12 male and 18 female students aged 15–16 years) in Garut, West Java. The intervention was conducted over four meetings using project-based learning supported by AR-based visualization and renewable energy prototyping activities. The research instrument consisted of 15 contextual multiple-choice items developed based on domain-specific critical thinking indicators. Data was analyzed using Rasch modeling to estimate students’ ability measures in logits. The results indicated a significant improvement (p < 0.001), with the average logit score increasing from -1.20 to 0.46 and an effect size of 1.64 (large). These findings suggest that IMOREAR enhances students’ critical thinking skills, underscoring its value in fostering 21st-century skills. Keywords: augmented reality, renewable energy, critical thinking skills, project-based learning, Rasch analysis